Kompetencje cyfrowe młodych dorosłych: modele ramowe a rzeczywiste profile kompetencji. Analiza przyczynkowa - Ogonowska, Agnieszka; Walecka-Rynduch, Agnieszka (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The aim of this article is to explain how young adults use their media competences to understand the digital reality in which they function on a daily basis. The article is preliminary in nature as it refers to the partial results of a larger research project on digital competences of young adults, which has been conducted since 2018 and concerns Polish users of the media sphere. The goal was to show the heterogeneous nature of the selected group in terms of competences necessary for the correct analysis, understanding and interpretation of media messages. In addition, the article highlights the importance of the cultural pattern and strategy of using online and interactive media in Poland. Their specificity results from actual deficiencies in the area of formal education. These shortages are related to the development of language, communication, media, digital and information skills at various stages of education (primary school, secondary school), which significantly affects the media competences of young adults.